Pelatihan dan Pendampingan Implementasi Rekam Medis Elektronik Nusa Medis untuk Meningkatkan Efisiensi Layanan di Klinik Baety Rahma - Frestiany Regina Putri; Sri Wulandari; Amindias Salsabila Swardani; Tina Rindiarum Dwinimastuti (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Information technology is any form of technology applied to process and transmit information in electronic form. This knowledge will help identify processes and prioritize scales, as well as assist in the formation of operational functions to support the optimization of Electronic Medical Records (EMR) implementation. Medical records are documented evidence issued by doctors regarding the diagnosis, actions, and medical services provided to patients. The implementation of electronic medical records is necessary to improve the quality and accelerate healthcare services. There are several approaches used in the implementation of the program, including presentations, demonstrations, and discussions. The solution offered in the Community Service activities for Baety Rahma Clinic is the implementation of EMR Nusa Medis as an effort to digitize medical record data. The final conclusion of this community service activity is that it ran smoothly and received positive feedback from the clinic staff. The outcome of the activity is that participants learned how to operate the EME Nusa Medis Software Application, particularly on the main clinic pages such as Outpatient, Pharmacy, and Cashier, which enhances the efficiency of medical data management, clinic operations, and patient services. In addition, the pharmacy and BHP features help consolidate the stock of medicines and consumables, thereby supporting the smooth operation of medical services.